Analisis Pembentukan Karakter Tanggung Jawab dalam Kegiatan Ekstrakurikuler Pendidikan Kepramukaan Bagi Siswa Sekolah Dasar - Icu Wahono; Lukman; Bambang Parmadi (Universitas Bengkulu, 2023)
This research aims to determine how the character formation of responsibility in scouting education extracurricular activities for elementary school students. This type of research is descriptive research with research methods namely qualitative research. The research subjects were scout groups in SD Negeri 08 Bengkulu City and SD Negeri 69 Bengkulu City. This research instrument using observation, interview and documentation guidelines. This research data collection technique using observation, interviews and documentation. The data obtained were analyzed through Data collection, Data Condensation, Data Display, Conclusion Drawing / Verification. The research aspect is focused on the activities of the opening ceremony of the Scouting for Community Scouts, the results of the study use 3 character indicators of responsibility: (1) exemplifies how to become good and proper ceremonial attendant to members of the scout movement (2) assigning duties to each scout member a heart- to- heart approach with thw practice girl. The conclusion of the study of responsibility character from those 3 indicatorc could lead to the character of that responsibility to the prescription- opening ceremony acrivities. Learners are responsible for assignments given by the patrons and can create good character responsibilities.